Accelerating the development of bioelectronic medicine: overview and impact of the NIH Stimulating Peripheral Activity to Relieve Conditions (SPARC) initiative - Katelynn A. Milora; Rebecca M. Black; Andrew C. Weitz; Michael B. Wolfson; Jessica Falcone; Eric Hudak; Brooks Gross; Nicholas Langhals; Sahana N. Kukke; Daniel Anthony Casco; Kristina Faulk; Julia Berzhanskaya; et al. (Bioelectronic Medicine, 2026)
Abstract The National Institutes of Health (NIH) Common Fund supports bold scientific programs that catalyze discovery across all biomedical and behavioral research to address high priority challenges for the NIH as a whole and make a broader impact in the scientific community. In 2015, the NIH Common Fund established the Stimulating Peripheral Activity to Relieve Conditions (SPARC) program. This program’s overall goal was to accelerate the development of neuromodulation, a field of study that uses bioelectronic devices to deliver electrical current to nervous system tissues to produce therapeutic effects in patients. Because the nervous system impacts all bodily functions, neuromodulation therapies have the potential to treat a variety of health conditions by regulating nerves that innervate affected bodily tissues and organs, with high specificity and few side effects. The SPARC program aimed to capitalize on recent advances in technology to deliver detailed, integrated functional and anatomical neural circuit maps for organs and to provide the necessary scientific foundation for clinical translation of more effective and advanced neuromodulation devices and stimulation protocols. Here we outline the SPARC program’s contribution to the field of neuromodulation over the past ten years, laying a comprehensive foundation of knowledge to inspire future research and accelerate translation. We discuss the reasoning behind the formation of the program, its structure, and outcomes.